MiR-206 Mediates YAP-Induced Cardiac Hypertrophy and Survival. Issue 10 (23rd October 2015) - Yang, Yanfei; Del Re, Dominic P.; Nakano, Noritsugu; Sciarretta, Sebastiano; Zhai, Peiyong; Park, Jiyeon; Sayed, Danish; Shirakabe, Akihiro; Matsushima, Shoji; Park, Yongkyu; Tian, Bin; Abdellatif, Maha; et al.
Abstract : Rationale: : In Drosophila, the Hippo signaling pathway negatively regulates organ size by suppressing cell proliferation and survival through the inhibition of Yorkie, a transcriptional cofactor. Yes-associated protein (YAP), the mammalian homolog of Yorkie, promotes cardiomyocyte growth and survival in postnatal hearts. However, the underlying mechanism responsible for the beneficial effect of YAP in cardiomyocytes remains unclear. Objectives: : We investigated whether miR-206, a microRNA known to promote hypertrophy in skeletal muscle, mediates the effect of YAP on promotion of survival and hypertrophy in cardiomyocytes. Methods and Results: : Microarray analysis indicated that YAP increased miR-206 expression in cardiomyocytes. Increased miR-206 expression induced cardiac hypertrophy and inhibited cell death in cultured cardiomyocytes, similar to that of YAP. Downregulation of endogenous miR-206 in cardiomyocytes attenuated YAP-induced cardiac hypertrophy and survival, suggesting that miR-206 plays a critical role in mediating YAP function. Cardiac-specific overexpression of miR-206 in mice induced hypertrophy and protected the heart from ischemia/reperfusion injury, whereas suppression of miR-206 exacerbated ischemia/reperfusion injury and prevented pressure overload-induced cardiac hypertrophy. miR-206 negatively regulates Forkhead box protein P1 expression in cardiomyocytes and overexpression of Forkhead box protein P1 attenuated miR-206–induced cardiac hypertrophy and survival, suggesting that Forkhead box protein P1 is a functional target of miR-206. Conclusions: : YAP increases the abundance of miR-206, which in turn plays an essential role in mediating hypertrophy and survival by silencing Forkhead box protein P1 in cardiomyocytes. Abstract : Supplemental Digital Content is available in the text.